Two-body abrasion wear mechanism of super bainitic steel. Issue 7 (3rd May 2017) - Guo, H.; Zhao, A.; Zhi, C.; Ding, R.; Wang, J.
Abstract : The abrasion wear resistance and wear mechanism of super bainitic steel austempered at different temperatures and time have been investigated by two-body abrasion testings, scanning electron microscopy, X-ray diffraction, transformation electron microscopy and electron backscattering diffraction. The results show that the two-body abrasion wear mechanism is predominantly micro-ploughing abrasion, and the wear resistance is decreased with increasing isothermal temperature which is attributed to the decreased hardness caused by a higher retained austenite content and the coarsening of the microstructure. The sample austempered at 230°C for 2 h with the higher amount of retained austenite and lower carbon concentration exhibits excellent wear resistance, and the transformation induced plasticity effect is observed during wear process which is beneficial for the improving of hardness and wear resistance.